FORMATION OF THE TEACHER IS WORKS OF CONCLUSION OF COURSE: THE CASE OF THE STATE UNIVERSITY OF LONDRINA (Fiep Bulletin - online, 2015)
This study had as general objective to contribute for the professionals' of Physical Education of the State University of Londrina formation, offering subsidies in process for the reformulate course and its implement, as guidelines of the Ministry of the Education opted for the qualitative and quantitative forms and we chose the case study, we believed to be this the technique that best characterized our investigation, because we intended to study facts that happened inside in a specific Course of a higher education institution. The 234 works of conclusion of course of the Course of Licenciatura were analyzed in Physical Education of the State University of Londrina, give in the years of 2000 and 2001. After the analysis of the works we verified that at 85,90% of the works were accomplished in the non school area. The Empiric-analytic abordagem went to more used in the works and the research line that more contributed with the works (52) it went to Pedagogy of the Sport. In the conclusion we presented subsidies for reformulação based on the literature and in the current legislation.
Keywords: .